Integrating Automatic Stock Monitoring and Digital Inventory Systems for MSMEs A Mobile Application Approach (Case Study in Serang City, Indonesia) - Rezty Arizta Putri; Salsanabila Mariestiara Putri; Hayatul Mardiah; Rizaldy Khair (Universitas Medan Area, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia continue to face inefficiencies in inventory management due to manual stock recording, data inconsistency, and delays in operational decision-making. In Serang City, these challenges often lead to stockouts, excess inventory, and limited business scalability. This study aims to develop and evaluate a mobile-based automated inventory management system that supports real-time stock monitoring and decision-making for MSMEs. The research employs a Research and Development (R&D) approach integrated with the Agile-Scrum methodology, encompassing problem identification, user requirement analysis, system design, prototype development, functional testing, and usability evaluation. Functional validation was conducted using black box testing, while system usability was assessed using the System Usability Scale (SUS) involving 15 MSME users. The results indicate that all core system functions achieved a 100% success rate, including automated stock recording, cloud-based data synchronization, real-time notifications, and dashboard analytics. The usability evaluation produced an average SUS score of 82.5, classified as Excellent, indicating high user acceptance and ease of use. These findings demonstrate that the proposed system effectively improves inventory accuracy, operational efficiency, and decision-making quality, contributing to MSME digital transformation in developing regions.